Pengembangan LKPD Digital Berbantuan GeoGebra Materi Persamaan Linear Satu Variabel untuk Mendukung Kemampuan Computational Thinking - Marta Risa Putri Utami; Hapizah; Budi Mulyono (Media Pendidikan Matematika, 2025)
In the digital era that requires young generations to think critically, creatively, and adaptively, Computational Thinking (CT) has become an essential skill for addressing 21st-century challenges. This study aims to develop a GeoGebra-assisted digital student worksheet (LKPD) on the topic of Linear Equation in One Variable (PLSV) using the context of smoking hazards to support students’ CT skills. The research employed a design research method of the development studies type, consisting of three phases: preliminary research, development or prototyping, and assessment, involving seventh-grade students from SMP Negeri 32 Palembang. Expert validation results showed an average validity score of 87.05% (very valid category), while the practicality test obtained 84.08% (practical category). Students found the digital LKPD engaging, easy to use, and helpful for understanding concepts through contextual videos and embedded GeoGebra explorations. Therefore, the developed digital LKPD is considered valid and practical, making it a feasible and innovative learning material to support students’ Computational Thinking skills in learning Linear Equations in One Variable.